Supplementing clinical diagnostics of erosive joint diseases with bio-inspired ratiometric sensors - Yang, Kylie; Pavic, Katrina; Bowyer, Amy A.; Manolios, Nicholas; New, Elizabeth J. (Frontiers in Sensors, 2022)
Inflammatory rheumatological disorders are often characterised by altered levels of matrix metalloproteinase levels in joint fluid and joint membranes. Therefore, monitoring of MMP activity in synovial fluid is essential to enable timely diagnosis, prognosis, and effective treatment. Here we report a novel fluorescence assay to measure protease activity in aspirated synovial fluid. Our fluorescent reporters contain cleavable linkers based on the peptide sequences of protease substrates, showing a ratiometric output upon cleavage. We have validated our reporters in patient-derived synovial fluid, and demonstrated their ability to characterise disease type.